FINANCIAL INCLUSION IN RURAL KERALA: A CASE STUDY OF CHERIYANADU PANCHAYATH - Gopalakrishnan, Sreedevi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Financial inclusion plays a pivotal role in fostering inclusive economic growth and poverty alleviation across developing economies. In India, significant strides have been made through policy interventions, technology-driven banking innovations, and community-based financial empowerment programs. This paper examines the extent and mechanisms of financial inclusion in Cheriyanadu Panchayath, Kerala, a state recognized for its superior human development indicators and progressive social policies. By surveying 50 rural households, this research analyzes the penetration of financial services, financial literacy levels, borrowing behavior, and the role of Self-Help Groups (SHGs) and government schemes. Findings indicate that MGNREGS-linked bank accounts, SHG participation, and high literacy have contributed to strong inclusion outcomes. However, substantial gaps in financial literacy and product diversification persist. Recommendations focus on enhancing financial advisory services, strengthening SHG-bank linkages, and promoting digital and investment literacy.